HEUTAGOGY AS A TRAINING APPROACH FOR TEACHERS IN THE ERA OF SOCIETY 5.0 - Ettyani Ettyani; Eka Fadilah; Yuliyanto Sabat (Magister Scientiae, 2023)
In the age of the 5.0 society era, a teacher's job description should include lifelong learners, learning leaders, instructors of learning resources, network builders, and communication facilitators. This study are to identify the difficulties that the 5.0 society era poses and present a heutagogical approach to teacher preparation and an overview of the implementation process. To achieve the goals, a thorough analysis of the literature was conducted. The findings showed that training programmes using a heutagogical approach should be taken into account because it is a self-determined learning process, and its implementation steps include enhancing digital literacy, developing a full and trustworthy learning management system platform, and implementing heutagogical teacher training. It is envisaged that heutagogy can be a substitute method of teacher preparation to create instructors who are ready for the learning difficulties of the society era 5.0.